Assessment of citrus susceptibility towards Candidatus Liberibacter asiaticus-Terengganu isolate based on vector and graft transmission tests. - Ahmad, Khairulmazmi; Sijam, Kamaruzaman; Hashim, Habibuddin; Abdu, Arifin; Rosli, Zamri (Canadian Center of Science and Education, 2011)
Khairulmazmi Bin Ahmad / Arifin Bin Abdu,Kamaruzaman Sijam,Zamri Bin Rosli / / Habibuddin Hashim